HISTOMORPHOLOGY OF KIDNEY OF EXPERIMENTAL ANIMALS AFTER MELOXICAM ADMINISTRATION - Kh. Ibraheem Al. Jubory, Raghad (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study investigates the deleterious effects of nonsteroidal anti-inflammatory drugs (NSAIDs), specifically meloxicam, on renal tissue in albino rats. Methods: Sixteen Sprague Dawley albino rats were divided into two groups: Group A received normal saline, while Group B was administered meloxicam at a dose of 15 mg/kg/day via a feeding tube for 14 days. On day 15, all animals were sacrificed, and their kidneys were extracted, preserved, and sectioned. The kidney samples were stained with silver methenamine, PAS, and H&E, and renal histology was examined under a light microscope to assess changes in the renal tubules. Results: The study found that meloxicam caused significant damage to the distal and proximal convoluted tubules in Group B rats. Notable histological changes included tubule dilatation, epithelial flattening, rupture of the brush border in proximal tubules, and thickening of the basement membrane surrounding the tubular epithelium. Novelty: This research highlights the nephrotoxic effects of meloxicam, a commonly used NSAID, providing new insights into its potential harmful impact on renal health, which has not been widely emphasized in previous studies on its adverse effects.